Tuning the properties of nitroxide spin labels for use in electron paramagnetic resonance spectroscopy through chemical modification of the nitroxide framework - Haugland, M; Anderson, E; Lovett, J (Royal Society of Chemistry, 2016)
Spin labels containing nitroxyl radicals possess many properties that render them useful for electron paramagnetic resonance (EPR) spectroscopy. This review describes the relationships between the structure and properties of nitroxide spin labels, methods for their synthesis, advances in methods for their incorporation into biomolecules, and selected examples of applications in biomolecule structural investigations.